Productiveness and yield components in dry season peanut as affected by planting time and calcium fertilization - Crusciol, Carlos Alexandre Costa; Lazarini, Edson; Golfeto, Alberto Ricardo; Sá, Marco Eustáquio de (Pesquisa Agropecuaria Brasileira, 2000)
The effect of Ca fertilization and sowing time on yield components and peanut pod yield in the dry season was studied. The experiment was conducted under field conditions in a Dark-Red Latosol, loamy texture, in Selvíria, MS, Brazil. Four sowing times (Jan. 21, Feb. 4, Feb. 18, and Mar. 4) were combined with four calcium levels (0, 45, 90 and 135 kg ha-1 of Ca), applied at the sowing time, into the furrows, utilizing dolomite limestone with PRNT 90.1% (21% of CaO and 18% of MgO). The number of pods per plant, number of grains per pod and per plant, 100 grains weight, hulled grains yield and peanut pod yield were determined. It is concluded that: 1) as the sowing is delayed, a water stress may occur in the growing period, and in the reproductive period, reducing the dry-season peanut crop productiveness; 2) there are good yields if planting is accomplished at the beginning of February; 3) the response for Ca fertilization is low in soils with high Ca level and medium basis saturation, specially when water conditions are also a limiting factor during dry season crop; 4) lime applied at the sowing time into the furrows is recommended.
Keywords: liming; crop yield; pods; weight